Logistyka organizacji sieciowych w handlu hurtowym w Polsce - Szuster, Mariusz (Logistics of Net Organizations in Wholesale Trade in Poland, 2005)
The author concentrates on forms of net organizations in wholesale trade in Poland. Apart from the dynamic development of the retail trade; the wholesale trade is an area which is to develop intensively in the next years. The article describes the logistic solutions, among others those which strengthen distribution. The tendency to decentralize the delivery process if foodstuffs which go bad quickly is visible. The nets of wholesale companies try to simplify to the maximum logistic solutions for them. In general every net adopts a logistic strategy which differs from other nets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 284-291